GRAMMATICAL ALLIANCE AND PIVOT SYSTEM OF BATAK SIMALUNGUN LANGUAGE: A SYNTACTIC TYPOLOGY STUDY - Lara Desma Sinaga; Mulyadi Mulyadi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
Syntax, morphology, and phonology can be used as a reference for language classification. This research aims to determine the grammatical alliance of the Simalungun language syntactically and its typology. It is a qualitative study with the typology approach. The data are phrases and clauses of the Simalungun language collected from informants and books – Simalungun language syntax books, by interviews and notes. It found that a transitive verb formulates the intransitive clause of the Simalungun Batak language as a predicate. The predicative verb appears with affixes. In general, the Simalungun language contains verbs that, in their presence, correspond to the subject. Simalungun language has a grammatical alliance system that treats subject (S) the same as agent (A), and a different treatment is given to predicate (P). Based on grammatical relations, the Simalungun language treats S the same as A at the syntactic level. Thus, it can be typologically grouped into syntactical accusatives. Based on the Pivot test, it also belongs to the accusative language group.